THE HISTORY OF FIEP IN BRAZIL (1949-2010) (Fiep Bulletin - online, 2012)
The history of FIEP in Brazil started in 1949 with the participation of a Delegation composed of 22 Brazilians who represented several states and attended the II STOCKHOLM LINGIADA - Sweden, from July 27 to August 13, 1949, when the FIEP World President, Major Joseph G. Thulin appointed the first FIEP Brazil Delegates, who took the opportunity to invite Prof. Thulin to visit Brazil and other South American countries, what happened the following year. Professors Alfredo Colombo (Rio de Janeiro and eastern Brazil); Sylvio José Raso (Minas Gerais and northern Brazil), Antonio Boaventura da Silva (São Paulo and western Brazil) and Jacintho Francisco Targa (Rio Grande do Sul and southern Brazil), are our pioneers, and had the responsibility to establish and structure FIEP in our country. In 1951 it was held in the city of Santos/SP the first course supported by FIEP Brazil. In 61 years, there have been 265 events with FIEP's logo in 24 states and 53 cities. Promotion, Support and Chancellery of events: Conferences, Tours, Seminars, Workshops, Forums, Meetings and Postgraduate courses. In Brazil, we had four World Congresses. The hallmarks of FIEP are the International Congresses of Physical Education held in Foz do Iguaçu, in Paraná State, Brazil. Since January 1986 to 2010, were 25th International Congress with the participation of over 52 thousand participants from 50 countries. FIEP Brazil makes history with their boldness and their actions for Physical Education. Our main projects are: FIEP INTERNET; Implementation of the FIEP STORE OF PHYSICAL EDUCATION; the FIEP PHYSICAL EDUCATION TEACHERS WITHOUT BORDERS PROJECT; the Implementation of the TVFIEP.COM PROJECT; the FIEP NEWSLETTER ON-LINE. FIEP also attended the implementation of the CONFEF/CREFs System, and we have delegates who are part of the Board of CONFEF, as well as several Federal and State Council members. The Delegates Office of Brazil supported the Movement for the Regulation of the Physical Education from the beginning, and helped officially launching the legislation movement in the International Congress organized by the Delegates General in Brazil, Foz do Iguaçu/PR, January 1995. We emphasize that the entrance into office of the council members of the 1st Federal Council of Physical Education - CONFEF was held at the Opening of the 14th International Congress on Education of FIEP in Foz do Iguaçu/PR, in thanks for FIEP's support to the Regulatory Movement, on January 10, 1999, at 9pm, headed by Prof. Edson Cardoso, current President of FBAPEF, attended by over 1500 Congress participants. FIEP has been a pioneering entity in the preparation of these Manifestos, highlighting the brilliant legacy of the directing document represented by the Physical Education World Manifesto - FIEP 2000, which is a reference for all reflections and actions in the area. The Brazilian professor Manoel Tubino was responsible for the introduction of the World Manifesto. In the Global Session, the following Brazilian professionals were elected to the FIEP World Board, term of 2000/2004: Prof. Dr. Manoel José Gomes Tubino (President), Prof. Almir Adolfo Gruhn (Secretary General) and Professor. Ms Paulo Ernesto Antonelli (Treasurer). Due to the good work, they were reelected in 2004/2008 and for 2008/2012, and after President Manuel Tubino passed away, the Secretary assumed the presidency until the end of his term in 2012. FIEP's Delegate Office in Brazil thanks all professionals who have provided volunteer services for the development of FIEP in Brazil, and spared no pains to attend the events, meetings and trips in these 61 years. Being a FIEP delegate is an achievement for our States, we become part of this great family that has responsibilities, rights and duties like any other institution. We are deeply grateful to the 310 teachers who have already been or are still part of the History of FIEP. Thank you very much! Our institution has Delegates in all of the states, and a Brazilian Committee of FIEP. The launch of the Book about the 60 years of FIEP in Brazil was a landmark that showed the history of FIEP Brazil in all states.